A switch in bidirectional histone mark leads to differential modulation of lincRNAs involved in neuronal and hematopoietic cell differentiation from their progenitors. Issue 5 (2nd January 2020) - Murad, Md. Wahid; Khan, Md. Abdullah‐Al‐Kamran; Islam, Md. Sajedul; Islam, Abul Bashar Mir Md. Khademul
Abstract: Long intergenic noncoding RNAs (lincRNAs) are more than 200 bases long, transcribed from intergenic genomic regions and do not undergo translation. They have regulatory roles in differentiation and development. However, how their transcription is activated and how their expression is differentially modulated in differentiation is quite unclear. In this study, we explored and analyzed data at the transcriptomic and epigenetic level to address these questions. Here, we identified novel lincRNAs that are differentially expressed in neuronal and hematopoietic differentiation and showed that such differential modulations are achieved under epigenetic regulations. lincRNAs that are upregulated in mature cells than in progenitor are activated from a bivalent poised state where activating H3K4me3/H3K9ac/H3K27ac and suppressive H3K9me3/H3K27me3 marks are colocalized. And, lincRNAs that are downregulated in mature cells after differentiation are suppressed by the addition of H3K9me3/H3K27me3 marks. Moreover, here we show a tissue‐specific expression pattern of lincRNAs in various cell lines and normal tissues. The study reveals bidirectional histone marks as an epigenetic means of directing the differential expression of lincRNAs which are found to be involved in the process of cellular differentiation. Abstract : In this study, first, the expression pattern of long intergenic noncoding RNAs (lincRNAs) in different cell lines and normal tissues was studied using RNA‐Seq data to get a global overview of their expression. Then, lincRNAs that are differentially expressed in neuronal and hematopoietic differentiation were identified. Finally, the roles of epigenetic means in this differential modulation were sought by analyzing chromatin immunoprecipitation (ChIP)‐Seq data of histone epigenetic marks. We hypothesized that differentially modulated lincRNAs that act in diverse epigenetic regulations in neuronal and hematopoietic differentiations are, themselves, epigenetically regulated by bivalent histone marks. The study reveals bidirectional histone marks as an epigenetic means of controlling the differential expression of lincRNAs involved in the process of differentiation.